Evaluasi Framework Pengembangan Web KinarBhusana: Studi Performance, SEO, dan Accessibility Menggunakan Laravel dan Bootstrap - Muhammad Daffa Al-farel; Akhmad Rizal Dzikrillah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Web programming skills are essential in today’s digital world for anyone who wants to work in the information and communication technology field. In order to attract clients and advertise their goods and services, every business must have a strong web presence. Companies need to use technology well in order to quickly adapt to digital changes and generate new value. Web platforms must meet important requirements in this regard, including excellent performance, search engine optimization (SEO), accessibility, and effective resource management. Due to their ease of use and effectiveness in producing dynamic and responsive website, frameworks such as Laravel and Bootstrap have gained popularity in web development. Thus, the purpose of this study is to assess how well Laravel and Bootstrap perform when building the KinarBhusana online application, with an emphasis on accessibility, SEO, and performance. It is hoped that the findings of this study will offer comprehensive insights into how well the frameworks perform in achieving these goals. The performance of the websites was compared before and after the frameworks were implemented using quantitative techniques and comparative study designs. This study's testing used Google Lighthouse which revealed that the results of using Laravel and Bootstrap were better in terms of performance, SEO, and accessibility of the KinarBhusana website.